Diagnosis and reform of public financial management systems: a key cross-cutting issue for program-based approaches in development policy - Stefan Leiderer (Deutsches Institut für Entwicklungspolitik (DIE), 2005)
In recent years public budgets have become an increasingly prominent issue in the international development debate. For one thing, more and more countries are developing poverty reduction strategies (PRS) or similar national development agendas that need to be translated into medium-term planning and allocation decisions, which in turn have to be implemented via the annual budget. For another, program-based approaches (PBAs), which primarily make use of recipients countries' own systems and procedures to manage donor funds, are assuming more and more importance in international development cooperation. The risks associated with budget support and other forms of PBAs hinge in crucial ways on the quality of partner countries' public financial management (PFM) systems. PFM systems in most developing countries are marked by substantial shortcomings. As a consequence, donors have developed a large set of diagnostic tools to assess PFM systems in developing countries. The tools are, however, beset by a variety of overlaps and omissions that tend to overstrain scarce capacities among both donors and partners and impact negatively on the quality of the diagnostic work undertaken. In addition, the predominantly donor-driven analyses of PFM systems focus primarily on the assessment of fiduciary risks related to different forms of PBAs and most of the time provide little indication as to the formulation of coherent and sustainable reform strategies. In the Paris Declaration on Aid Effectiveness both donors and recipient governments have committed themselves to developing common frameworks for assessing PFM systems and to systematically integrating these frameworks within partner-led reform and capacity-building strategies. Under the Public Expenditure and Financial Accountability Program (PEFA), several donors have been involved in developing just such a common framework to assess and reform PFM systems in developing countries, Effective and sustainable PFM reform, however, constitutes a considerable challenge for all parties involved. PFM systems are highly path-dependent, and reforming them is first and foremost a political task. Effective reform strategies therefore require strong commitment by all stakeholders, maintenance of momentum for reform over a protracted period of time, a large measure of partner ownership for the reform process, and a willingness on the part of donors to work for extensive coordination, harmonization, and division of labour.
Keywords: 330